Effects of hot-air and vacuum drying on drying kinetics, bioactive compounds and color of bee pollen - Kayacan, Selma; Sagdic, Osman; Doymaz, Ibrahim (SPRINGER, 2018)
This study aims to investigate drying kinetics of bee pollen as thick as 5 mm and change of color, total phenolic content, total flavonoid content, and antioxidant capacity of fresh and dried bee pollen by using both hot-air and vacuum drying at 40, 45 and 50 degrees C. Six well-known thin-layer drying models were used to predict drying kinetics by nonlinear analysis of regression. The Midilli & Kucuk model best fitted the experimental data for the whole range of temperatures. The moisture diffusivity coefficient at each temperature was determined by Fick's second law of diffusion, in which their value varied from 8.40 x 10(- 11) to 6.29 x 10(- 10) m(2)/s over the mentioned temperature range. The dependence of effective diffusivity coefficient on temperature was expressed by an Arrhenius type equation. The calculated values of the activation energy of moisture diffusion were 49.47 and 33.57 kJ/mol for hot-air and vacuum dryers, respectively. After drying processes, total phenolic content, total flavonoid content and antioxidant activity of bee pollen decreased. Higher total phenolic and total flavonoid content values were obtained in a vacuum drying at 45 degrees C. In addition, the total color change of bee pollen dried at vacuum conditions was lower than dried at hot-air conditions.
Keywords: Bee pollen; Vacuum drying; Hot-air drying; Mathematical drying; Bioactive properties; ANTIOXIDANT ACTIVITY; EXTRACTS; QUALITY; POLYPHENOLS; KIWIFRUIT; PROPOLIS; CAPACITY; SLICES; MODELS; Food Science & Technology